Profitability Analysis of Insurance Products from Polish Market in the Period 2006-2008 - Chmielowiec-Lewczuk, Magdalena (Analiza rentowności produktów ubezpieczeniowych na przykładzie polskiego rynku w latach 2006-2008, 2010)
The aim of the paper is an analysis of insurance products profitability on the basis of data presented in reports by Polish Financial Supervision Authority. That is why insurance products division is the same as in regular insurance classification which is based on legislation insurance act. Information about costs and incomes is taken from financial statements of Polish insurance companies. Insurance guarantees and credit insurance are the most profitable products for the insurance companies and the worst insurance product is annuity
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 145, s. 15-24
Keywords: premiums; paid claims; insurance activity costs